Nonaqueous electrocatalytic water oxidation by a surface-bound Ru(bda)(L)2 complex. Issue 15 (14th March 2016) - Sheridan, Matthew V.; Sherman, Benjamin D.; Wee, Kyung-Ryang; Marquard, Seth L.; Gold, Alexander S.; Meyer, Thomas J.
Abstract : Electrocatalytic water oxidation by a heterogeneous Ru(bda) catalyst is enhanced in a non-aqueous environment relative to water as the solvent. Abstract : The rate of electrocatalytic water oxidation by the heterogeneous water oxidation catalyst [Ru(bda)(4-O(CH2 )3 P(O3 H2 )2 -pyr)2 ], 1, (pyr = pyridine; bda = 2, 2′-bipyridine-6, 6′-dicarboxylate) on metal oxide surfaces is greatly enhanced relative to water as the solvent. In these experiments with propylene carbonate (PC) as the nonaqueous solvent, water is the limiting reagent. Mechanistic studies point to atom proton transfer (APT) as the rate limiting step in water oxidation catalysis.